WALDORF SCHOOL IN THE LIGHT OF OPTIMIZATION EDUCATIONAL PROCESS JUNIOR SCHOOL STUDENTS IN NATIVE LANGUAGE LESSONS (Pedagogy of Higher and Secondary Education, 2003)
The article deals with one of the most effective directions of teaching the native language at a contemporary school. The authors give us different perspectives on the peculiarities of learning and upbringing at Vuldorphsky school. They pay attention to its prospects and make an accent on its expediency at Modem Didactics.